Minimization of DC-link voltage variation in a hydraulic turbine generation system using back-to-back converters - Jeon, Sung Soo; Bak, Yeongsu; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2019)
This paper proposes minimization method of DC-link voltage variation in a hydraulic turbine generation system using back-to-back (BTB) converters. When the generation power is drastically changed, it causes the variation of the DC-link voltage. It deteriorates stability and efficiency of the hydraulic turbine generation system. This paper describes how the compensation current is calculated to reduce the variation of the DC-link voltage. The stability and efficiency of the hydraulic turbine generation system can be improved through the proposed compensation current. The proposed method was verified through the simulation and experimental results.
Keywords: Back-to-back converter; Compensation currents; DC-link voltages; Generation systems; Minimization methods; Back-to-Back Converter; Compensation Current; DC-Link Voltage Variation; Hydraulic Turbine Generation System